The Application of CHSE to Visitor Satisfaction in Jakarta’s Tourist Attraction in The New Normal Era - Liliana Dewi; Ni Wayan Faustina (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of the implementation of clean, health, safety and environment sustainability (CHSE) on visitor satisfaction in the tourist attractions of the city of Jakarta. The research method used is a descriptive quantitative approach. Population and sample as many as 100 respondents who visited five attractions in Jakarta. The result is that the application of CHSE has a significant influence on visitor satisfaction.